O conceito de "inteligência espiritual" - Mendes, Mary Jane Shalders Pereira (2017)
This dissertation presents a neologism from the perspective of the science of religion, spiritual intelligence. Spiritual intelligence suggests it may be one of various types of intelligence and that can be built regardless of the IQ level. Spiritual intelligence needs a deepening of self-integration of the inner life of mind and spirit with the outer life of work in the world, both personal and professional, showing that they are not different behaviors. It can be cultivated through spiritual practices and the apex is the express spiritual maturity through true perception (wisdom and meanings) before the choices. What itself contributes to the insight in making assertive choices that contribute to their own well-being and his neighbor. Spiritual intelligence can be developed everywhere, inside and outside of religious traditions regardless of belief, in the workplace and living in society